The Calls for Universal Social Protection by International Organizations: Constructing a New Global Consensus - Lutz Leisering (Social Inclusion, 2020)
Universalism has become a lead idea of global social politics, and of global social security in particular, first voiced in the Universal Declaration of Human Rights of 1948 and renewed in recent calls for “Social Security for All” and “Universal Health Coverage,” and in the Global Partnership for Universal Social Protection to Achieve the Sustainable Development Goals launched by the World Bank and the International Labour Organization in 2016. This article analyses the idea of a universal right to social protection, as recently articulated by international organizations. According to J. W. Meyer’s neo-institutionalist theory of world society (Krücken & Drori, 2009; Meyer, 2007), universalism is a world-cultural norm, and international organizations are proponents of world culture. This article is based on the assumption that the meaning of universalism is not fixed, but that international organizations construct the norm in changing ways to secure worldwide acceptance and applicability, considering that states have very diverse socio-economic conditions and socio-cultural backgrounds. Accordingly, the article analyses how international organizations construct the cultural idea of universalism as well as institutional models of universal social protection. The finding is that the recent calls for universalism represent a new interpretation of universalism that refers to individual entitlements to benefits rather than collective development, and that this global consensus was reached by constructing the norm in a way to leave room for interpretation and adaptation. However, the price of consensus is the attenuation of the norm, by allowing particularistic interpretations and by weakening the content of the right to social protection. The article also seeks to explain the rise of the new global consensus and identify its limitations.